Hubungan Negara-Ummah Dalam Hukum Indonesia Dan Islam - M. Nur Kholis Al-Amin; Nurjidin Nurjidin (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2017)
Through legal references review, the present study aimes at finding out the concept of ummah in the Medinah Charter and the concept of nation state in the Jakarta Charter (Indonesia’s 1945 Constitution) along with the correlation between the two. The conclusion is that, as constitution, the Medinah Charter is as sililar as the Jakarta Charter or the 1945 Constitution in the context of Indonesia, which has a feature of equations. From the historical point of view, both were grew out of a plural society which then formed a whole community in one melting pot, that is governance or state. In its values, ​​both contains the recognition of plurality of society and the principles of equality, unity, justice in one community